Analisis Kesalahan Konseptual Mahasiswa Pendidikan Matematika Dalam Menyelesaikan Materi Fungsi Dalam Bilangan Real - Lubis, Nazlah Indri Agistia; Zendrato, Mikhah Adillah; Ndor Damayanti Silalahi; Rizki, Putri; Christian Simanullang, Michael (Pendidikan Matematika FKIP Universitas Mataram, 2025)
This study was conducted with the aim of describing the forms of conceptual errors made by Mathematics Education study program students in solving set and function problems in real numbers, and analyzing the causes of errors made. The research method used was qualitative with descriptive method. The research subjects consisted of five students who were randomly selected, with the condition that they had taken related courses but still showed errors in working on problems. Data were collected through a questionnaire test designed to reveal students' conceptual understanding and analyzed using Kastolan's error classification. The results showed that procedural error was the most dominant type of error, with a percentage of 60%. Conceptual errors and technical errors each had a percentage of 20%. This finding shows that students still have difficulty in following the steps of solving problems coherently, understanding basic concepts, and performing calculation operations carefully. Therefore, improvement is needed in learning strategies that emphasize concept understanding, procedural accuracy, and technical accuracy